Analisis Strategi Pemasaran Dalam Meningkatkan Jumlah Kepesertaan Bukan Penerima Upah (BPU) Studi Kasus BPJS Ketenagakerjaan Cabang Padangsidempuan - Sovia Harahap; Zuhrinal M. Nawawi; Nurul Inayah (Jurnal Manajemen Akuntansi (JUMSI), 2023)
Membership of Non-Wage Recipients in BPJS Ketenagakerjaan at the Padangsidempuan Branch office has decreased in 2019. Many branch offices have not been able to achieve the participation target, especially Non-Wage Recipient membership. The lack of knowledge of these self-employed workers regarding BPJS Employment considers that BPJS Employment is only for formal workers only those who work with agencies or companies and interactions and information related to membership of non-wage earners are limited, making it difficult for workers. The type of research used by researchers is field research using a qualitative approach. Data collection techniques used by researchers are interviews and observation. The results of this study are that Employment BPJS implements a marketing strategy that is able to change employment conditions by taking advantage of existing opportunities and minimizing threats from outside the company. The strategies used are extensification, intensification, and retensification strategies. And other efforts made by Employment BPJS to expand membership are taken through the private sector in providing protection for workers. Conduct intensive educational and outreach activities to business actors and workers to increase awareness. Regarding improving the quality of services, BPJS Employment has optimized the simplification and standardization of claims processes and services that are safe and very easy through the JMO (Jamsostek Mobile) application, and Bukalapak Asik (service without physical contact), as well as increasing engagement and retention with participants.